PENGARUH QUALITY OF WORK LIFE TERHADAP QUALITY LIFE KARYAWAN PT PELINDO III (PERSERO) TPKS - Anggy Antari Dilaningrum; Rara Ririn Budi Utaminingtyas; Inayah - Inayah (Admisi dan Bisnis, 2018)
The research aims to analyze the influence ofQuality of Work Life on Quality of Life case study on operator employee of Container Crane and Rubber Tyre Gantry PT Pelindo III (Persero) Terminal Petikemas Semarang. The independent variables of this research are Occupational Health and Safety, Compensation and Work Environment while The dependent variable is Quality of Life. The methods of data collection are questionnaire completion, direct observation and literature review. The sample of this research are 70 respondents and instrument tests used are the validity test and reliability test. The technique of analysis used in this research were multiple linear regression analysis and classic assumption test. The result of multiple linier regression analysis could be shown by the regression equation Y=27,213+0,605X1+0,463X2+0,824X3. Coefficient determination in this research was0.592, which meant that 59.2% of heavy equipment operator’s Quality Life could be influenced by Occupational Health and Safety, Compensation and Work Environment, whereas the remaining of 40.8% is influenced by others variables which are not observed in this research. The result of this research shows that Quality of Work Life had positive and significant influence at the same time on Quality of Life and the most influencing variable on Quality of Life is Work Environment